Evaluation of miRNAs targeted RBPs under hypoxia in cancer - CHAUDHARY, NISHANT (The Indian Journal of Animal Sciences, 2019)
Micro RNAs (miRNAs) are miniature, non-coding RNA molecules which are implicated in post-transcriptional regulation of genes. RNA binding proteins (RBPs) are involved in a diversity of functions including posttranscriptional regulation of genes. They have also been exposed to influence the messenger RNA stability by binding to their identified sequences at the 3’ untranslated region (UTR). Specific RBPs and miRNAs uncovered to be key participant in hypoxia signaling which is present in cancer cells, have been shown to involve in the outcome of the cell and drive towards tumor aggressiveness. Since both RBPs and miRNAs have been shown to be overstated by hypoxia and additionally significant since the site of battle of both players are the same (3’UTR of mRNA), we suggests that they might have role in tandem or be occupied in each other’s regulation. Stem loop qRT-PCR was used to check the expression levels of these target miRNAs and the corresponding RBPs in cancer cell lines, namely U87MG (Glioblastoma) and MCF7 (Breast cancer) under hypoxic and normoxic conditions. Transient over expression of the aforesaid miRNAs in the two cancer cell lines was examined using qRT-PCR to see the regulatory effects of these microRNAs on the corresponding target RBPs. Taken together, our results advocate that there could possibly be communication between the miRNA-RBP pairs that we had chosen and assessing the possibility as therapeutic agents for treatment of various cancers will depend upon suitable animal model.